Utilization of Modern Contraceptives among HIV Positive Reproductive Age Women in Tigray, Ethiopia: A Cross Sectional Study. (24th September 2013) - Berhane, Yemane; Berhe, Haftu; Abera, Gerezgiher Buruh; Berhe, Hailemariam
Abstract : Background . HIV infected women in sub-Saharan Africa are at substantial risk of unintended pregnancy and sexually transmitted infections. In developing countries including Ethiopia counseling and provision of modern contraceptives of choice to HIV infected women including those on antiretroviral therapy (ART) is an important strategy to prevent unintended pregnancies and sexually transmitted infections. Little is known about the existing practices and utilization of modern contraceptives among HIV positive reproductive age women attending ART units. Objective . The aim of this study was to assess utilization of modern contraceptives and associated factors among HIV positive reproductive age women attending ART units in zonal hospitals of Tigray region, North Ethiopia. Method . Institution based cross-sectional study was conducted by interviewing 364 HIV positive reproductive age women in all zonal hospitals of Tigray region using systematic sampling technique. Structured and pretested questionnaire was used to obtain information from the respondents. Descriptive, bivariate, and multivariate methods were used to analyze utilization of modern contraceptives and the factors associated with it. Result . Three hundred sixty-four subjects participated with a response rate of 99.2%. The mean age of the respondents was31.9 ± 6.5 (SD) years. About 46% of participants utilized modern contraceptives, 59.9% out of them used dual method. However, a significant proportion of the respondents (46%) reported that they wished to have a desire for children. Being secondary education and higher (AOR: 2.85; 95% CI: 1.17–6.95) and currently on HAART (AOR: 3.23; 95% CI: 1.49–7.01) they were more likely to utilize modern contraceptive. But those women who were ≥25 years old, house wives, single, divorced, or widowed were less likely to utilize modern contraceptive. Conclusion . Results of this study revealed that the number of respondents who were ever heard of modern contraceptives was high. However, modern contraceptive utilization was still low. Additional efforts are needed to promote modern contraceptive utilization in general and dual method use in particular among HIV positive reproductive age women.